Towards the Development of a Framework for Assessing Organizational Governance Maturity for Technical Audit of Public Works - Haule, George C.; Matindana, Juma M. (Tanzania Journal of Engineering and Technology, 2025)
The quality of the audit work and its products is often associated with the organizational maturity of the audit function. The absence of a well-defined organizational maturity for an audit function leads to poor quality of audit work or products and ineffective audit function. The lack of a framework for measuring governance maturity was identified as a major deterrent factor to the attainment of quality audit work. Measuring the governance maturity of the technical audit of public works is challenging due to the absence of a maturity framework that fits its needs. The noted shortcomings include: (a) existing maturity frameworks used to assess organizational maturity have not been developed based on standards and requirements governing technical auditing; (b) defined technical competency for technical auditors, work methods and processes have not been covered in those frameworks rather focused on other types of audits than technical audits; and (c) the institutional framework considered in those frameworks are not applicable in technical auditing. The challenges impede the ability of the technical audit function to establish relevant and reliable criteria to measure governance, and it largely affects the growth of the technical audit functions and the quality of audit works. This paper provides a theoretical overview of what, why and how a framework can be developed for assessing the level of organizational governance maturity for technical audits of public works.